Challenges and Opportunities for the Surabaya City Government in Infrastructure and Social Development in the Regional Autonomy Era - Yudha, Ragiel; Agus Widiyarta (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Abstract This study examines the challenges and opportunities faced by the Surabaya City Government in realizing infrastructure and social development in the era of regional autonomy. Using qualitative research methods, this study analyzes the city government's strategies in overcoming budget constraints, managing urbanization, and optimizing the use of technology in governance. The results of the study show that the Surabaya City Government has implemented various innovative strategies such as public-private partnerships, optimizing local revenues, and implementing e-Government to overcome development challenges. Despite facing problems such as rapid urbanization and budget constraints, Surabaya has succeeded in utilizing opportunities through smart city development, increasing community participation, and implementing technology in public services. This study concludes that Surabaya's success in sustainable development depends on the city government's ability to continue to innovate and adapt to change, as well as increasing collaboration with various stakeholders.  Keywords: Regional Autonomy, Infrastructure Development, Urbanization, Smart City.